Tumbo z Mysu dobrej nádeje - Centkiewiczowa, Alina, 1907-1993; Centkiewicz, Czesław Jacek, 1904-1996; Babiaková-Bajová, Mária, 1914-1993 (Bratislava Mladé letá, 1968)
Beletria
Keywords: umelecká literatúra